Gestión Publicitaria en el comercial Yahveh del Cantón Babahoyo Provincia de Los Ríos, período 2023 - 2024. - Guerrero Bajaña, Luisana Katherine (2024)
Comercial Yahveh Jireh, located in Babahoyo, faces significant challenges in its digital marketing management due to the absence of a specific department and lack of training in this area, resulting in limited visibility and sporadic, poorly directed campaigns. This study aims to diagnose the internal and external factors influencing the company's digital advertising, evaluate the effectiveness of the implemented strategies, and propose improvements to optimize its online presence. The analysis results reveal an intermediate situation, with a weighted score of 2.32 in the EFI and 2.55 in the EFE, indicating that while there are strengths such as strategic location and product variety, there are also critical weaknesses, such as the lack of a digital marketing department and limited staff knowledge in this area. Externally, the growth of e-commerce and increasing use of social media present key opportunities, whereas high competition and rapid changes in online consumption trends pose significant threats. The conclusions emphasize the need to implement strategies to address these weaknesses and leverage the opportunities. It is recommended to create a specialized digital marketing department, train staff in the latest marketing trends and tools, allocate a specific budget for these activities, and improve internal communication. Additionally, it is crucial to develop an effective marketing calendar and explore collaborations with local influencers to increase the commercial's visibility and reach. With these actions, Comercial Yahveh Jireh can significantly improve its digital marketing management, strengthen its market presence, and enhance its competitiveness in Babahoyo's digital environment.